Philosophical myths of the fall - Mulhall, Stephen, 1962- (Princeton monographs in philosophy., 2007)
Did post-Enlightenment philosophers reject the idea of original sin and hence the view that life is a quest for redemption from it? In Philosophical Myths of the Fall, Stephen Mulhall identifies and evaluates a surprising ethical-religious dimension in the work of three highly influential philosophers--Nietzsche, Heidegger, and Wittgenstein. He asks: Is the Christian idea of humanity as structurally flawed something that these three thinkers aim simply to criticize? Or do they, rather, end up by reproducing secular variants of the same mythology? Mulhall argues that each, in different ways, develops a conception of human beings as in need of redemption: in their work, we appear to be not so much capable of or prone to error and fantasy, but instead structurally perverse, living in untruth. In this respect, their work is more closely aligned to the Christian perspective than to the mainstream of the Enlightenment. However, all three thinkers explicitly reject any religious understanding of human perversity; indeed, they regard the very understanding of human beings as originally sinful as central to that from which we must be redeemed. And yet each also reproduces central elements of that understanding in his own thinking; each recounts his own myth of our Fall, and holds out his own image of redemption. The book concludes by asking whether this indebtedness to religion brings these philosophers' thinking closer to, or instead forces it further away from, the truth of the human condition. --From publisher's description.